Strategies of Translating Quranic Culture-Specific Expressions: A Case Study of Shakir and Arberry's Translations - Thawabah, Hind Morshed Abdullah (University of Science and Technology, Sana'a, 2019)
This study aimed to investigate the translations of Quranic culture-specific expressions into English. This included the used translation strategies, the frequency of each used strategy and the reasons behind the difficulty in translating Quranic culture-specific expressions into English. To attain the objectives of the study, a sample of thirty culture-specific expressions were selected from the Holy Qur’an along with their translations into English by the translators Shakir and Arberry. These expressions were classified into three categories, namely; religious, social and environmental by using Ivir’s model for translating culture-specific expressions. A qualitative and quantitative analytical approach was adopted for the purpose of data analysis. The results obtained from this study demonstrated that Quranic culture-specific expressions are amenable for translation by specific strategies in which “literal translation” was the most used strategy. The selection of translation strategies seemed to rely on the category of these references, for which 'Borrowing' was found the most frequent strategy for translating environmental expressions. The results also revealed that the difficulties of translating Quranic expressions varied according to their attributes. For instance, there were difficulties resulted from the cultural gap between the source language and the target language, in general, and from the eloquent style of the Holy Qur’an, in particular. In addition, the translators’ cultural backgrounds were found to have a remarkable influence on the selection of translation strategies.
Keywords: Quranic Translation; Culture-Specific Expressions; Shakir; Arberry; Translation Strategies